The Effect of Plastic Waste Attachment on Branching Coral to Zooxanthellae Abundance in the Kelapa Dua Island Waters, Seribu Islands - Fadel Muhammad; Neviaty Putri Zamani; Meutia Samira Ismet; Muhammad Irlan Assidiq Kusuma Ramadhan (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
HighlightLight intensity from plastic waste was positively correlated with the abundance of zooxanthellae in corals.The abundance of zooxanthellae between sack plastic and clear plastic treatment tended to be the same.The treatment of packaging plastic was treated with the lowest light intensity.The treatment of black plastic was the treatment that produced the lowest abundance of zooxanthellae. AbstractCoral growth in Indonesia was being disrupted due to the continued threat of environmental change, such as littering to the beach. This study aimed to analyze the effect of the attachment of different colored plastic waste to the rate of zooxanthellae abundance on branching corals in Kelapa Dua Island waters. Branching coral colony samples consisted of the genus Acropora and Porites with a total of 15 fragments of coral colonies at the depth of 80-90 cm were tested with a treatment of the attachment plastic wastes (control, clear plastic, plastic sack, plastic packaging, and black plastic) for four days. The zooxanthellae abundance was calculated using the APHA (American Public Health Association) formula. The results of zooxanthellae abundance on the closure treatment of branching coral samples with black plastic and control had the lowest and highest values by 4.25 x 105 cells/cm2 and 1.38 x 106 cells/cm2. The results of the linear regression test showed that there was a significant relationship between plastic waste with low light intensity and a decrease of zooxanthellae abundance in coral colonies with the equation Y of 972.78x + 653402, determination index (R2) of 0.68, and correlation index (r) of 0.83. These results indicated that the attachment of plastic waste to branching coral colonies could be a stressor on coral animals in reducing light intensity, which caused a reduction of zooxanthellae abundance as coral endosymbiont.